Penerapan Quizizz Bernuansa Etnomatematika Melalui Problem Based Learning Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa - Shofiyul Annisa; Zaenuri Zaenuri; Kustiono Kustiono; Mochamad Guntur (Universitas Negeri Padang, 2023)
The research aims to determine the effectiveness of students' mathematical critical thinking skills using quizizz with PBL with ethnomathematics nuances. The type of research that has been used is quantitative with quasi-experimental methods. One group pretest-posttest research design. Students are given a pretest and intervention through the use of quizizz, after which a posttest is carried out. The research sample was 55 grade IV elementary school students using the saturated sampling technique. The research instrument was a multiple choice test, while data analysis used an independent sample T-Test with a difference test of Sig = 0.000. The results showed that the experimental class mean was 80.82, the control class was 74.14. This proves that the application of quiziz in PBL with ethnomathematics nuances is very effective in increasing student learning independence (self-confidence, always prepared, daring to appear in front, confident in one's abilities, and not afraid to try). Therefore, the application of quiziz with PBL with ethnomathematics nuances can improve students' critical thinking skills.